Family-to-work conflict linked to psychological distress and family life satisfaction during the second year of the COVID-19 pandemic in dual-earner parents with adolescents - Schnettler, Berta; Miranda-Zapata, Edgardo; Orellana, Ligia; Saracostti, Mahia; Poblete, Héctor; Concha-Salgado, Andrés; Lobos, Germán; Adasme-Berríos, Cristian; Lapo, María; Beroiza, Katherine; Riquelme-Segura, Leonor; Sepúlveda, José A.; et al. (Frontiers in Public Health, 2024)
IntroductionResearch on work-family dynamics during the COVID-19 pandemic shows that family demands increased for workers, particularly those with children. This heightened family-to-work conflict negatively affects the subjective well-being of parents and their children. However, these outcomes have been mainly examined on individuals without considering the family as the unit of analysis. This study aimed to explore the relationships between family-to-work conflict, psychological distress, and family life satisfaction in dual-earner parents with adolescent children during the second year of the COVID-19 pandemic. Moreover, the potential mediating role of psychological distress among FtoWC and family life satisfaction and the moderating role of household monthly income were tested.MethodsThe non-probabilistic sample in Chile comprised 860 dual-earner parents and one of their adolescent children (mean age 13.5 years, 50.8% female). Parents answered an online questionnaire with FtoWC scale, whereas parents and adolescents answered the Depression, Anxiety, Stress Scale and the Satisfaction with Family Life Scale. Analysis was conducted using structural equation modeling and the mediation actor-partner interdependence model.ResultsFtoWC was directly linked to lower family life satisfaction in fathers and via a mediating role of psychological distress in both parents. Mothers’ FtoWC was related via the mediating role of the fathers’ psychological distress to fathers’ lower family life satisfaction and via the mediating role of the adolescents’ psychological distress to adolescents’ lower family life satisfaction. Monthly household income moderated three APIM model paths involving mothers’ variables.DiscussionThese findings underscore the importance of implementing family-oriented workplace policies. Such policies may help mitigate both parents’ experiences of FtoWC and their resulting psychological distress.